Optimization strategy for social media content to enhance branding and sales of MSME in Samarinda - Surahman, Surahman; Hariyadi, Sugeng; Barus, Bela; Dwiyanti, Septiani Anggun; Irawan, Imelda; Hastuti, Putri Widya; Fatiya, Nasywa Nur; Mauliahasmi, Siti (Community Empowerment, 2025)
This community service activity was executed to optimize digital marketing effectiveness and increase sales for the Amplang Bukuan Snack MSME in Samarinda. The main problem addressed was low brand visibility and insufficient online sales, resulting from sub-optimal utilization of social media. The intervention strategy implemented involved integrated training on: (1) optimizing social media (Instagram) and creating appealing visual content; (2) creating and managing an online store on the Shopee platform; and (3) implementing the non-cash payment system QRIS. The results of the service demonstrate a significant increase in digital performance and sales. Within two months following the intervention, the Instagram account’s engagement rate increased by 65%, accompanied by follower growth from 320 to 530. The average interaction per post (likes and comments) rose from 12 to 38, reflecting higher audience involvement. Simultaneously, the number of online orders via direct message (DM) increased by 28%. Furthermore, the MSME owner’s competency in digital marketing significantly improved, as shown by an increase in the knowledge assessment score from 56% to 84%. These findings indicate that the systematic optimization of social media content successfully enhanced brand visibility, directly contributed to sales growth, and strengthened the digital entrepreneurial capacity of MSME.